2023
DOI: 10.3897/tuhinga.34.98329
|View full text |Cite
|
Sign up to set email alerts
|

South American terrestrial Gastropoda in the collection of the Auckland War Memorial Museum

Abstract: The catalogued collection of South American terrestrial gastropods, including the Caribbean ABC islands and Trinidad & Tobago, of the Auckland War Memorial Museum (AM), New Zealand, is discussed here. In total, 264 specimen lots from South America were found in the AM collection, including eight type lots. Twelve of the specimens represent new geographic distribution data, including the first known precise locality for the species Bostryx luridus (L. Pfeiffer, 1863) and potentially for Drymaeus cf. waldosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Still, the genera Leiostracus and Simpulopsis are not monophyletic and need a thorough revision. Two further genera, even though not represented in our study, likely belong in this family as well: Lopesianus Weyrauch, 1958 and Eudioptus Martens, 1860 (see discussion in [ 57 ]). Simpulopsidae is neotropical, with only a few species present in the sub-tropical areas of South America (e.g., [ 32 , 58 ]).…”
Section: Discussionmentioning
confidence: 94%
“…Still, the genera Leiostracus and Simpulopsis are not monophyletic and need a thorough revision. Two further genera, even though not represented in our study, likely belong in this family as well: Lopesianus Weyrauch, 1958 and Eudioptus Martens, 1860 (see discussion in [ 57 ]). Simpulopsidae is neotropical, with only a few species present in the sub-tropical areas of South America (e.g., [ 32 , 58 ]).…”
Section: Discussionmentioning
confidence: 94%
“…Despite being such a remarkable species, P. gayi has rarely been recorded attacking, preying on, or ingesting other invertebrates. Herein, we report two events of P. gayi preying on black snails, Macrocyclis peruvianus , the only extant representative of the family Macrocyclidae (Salvador et al, 2021). This snail is found in Chile, between the Maule and Aysén regions, and in neighbouring areas of Argentina, in the Neuquén province and the Bariloche department of the Río Negro province, overlapping with the known distribution of P. gayi (Barahona‐Segovia, 2019; Salvador et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with healthy cordilleran and coastal forests (Gómez et al, 2020), found in the forest soil among ferns, moss, liverworts and even under fallen logs (Silva & Thomé, 2009). The shell is recognizable by its shape and size: depressed, with whorls rapidly increasing in size, reaching 50–60 mm in diameter (Salvador et al, 2021; Silva & Thomé, 2009). Similar to the case of P. gayi and other invertebrates of Chilean forests, the ecology of M. peruvianus is poorly known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation